2003
DOI: 10.1080/14660820301185
|View full text |Cite
|
Sign up to set email alerts
|

Reduced p75 NTR expression delays disease onset only in female mice of a transgenic model of familial amyotrophic lateral sclerosis

Abstract: hSOD1 (G93A) transgenic mice develop pathological changes similar to those in patients with familial amyotrophic lateral sclerosis (FALS). In particular, the progressive degeneration of motoneurons is charactered in this mouse model. One feature of stressed motoneurons in ALS and the hSOD1 mice is the induction of the p75 neurotrophin receptor, which is thought, under certain circumstances, to be a death-signaling molecule. We have studied disease progression of hSOD1 (G93A) mice in the absence of the p75NTR r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Alternatively, AS-PNA may act on other neural cell types. Changes in glial cell proliferation and activation were recently reported in SOD1 G93A double transgenic mice genetically deficient in p75 NTR expression (Kust et al 2003). Extended survival was determined in female mice only, explained by reduced astrogliosis in the spinal cord.…”
Section: Discussionmentioning
confidence: 89%
“…Alternatively, AS-PNA may act on other neural cell types. Changes in glial cell proliferation and activation were recently reported in SOD1 G93A double transgenic mice genetically deficient in p75 NTR expression (Kust et al 2003). Extended survival was determined in female mice only, explained by reduced astrogliosis in the spinal cord.…”
Section: Discussionmentioning
confidence: 89%
“…Our results suggest that there is a set of signaling factors that are altered, rather than a single pathway that is affected. These observations may explain the limited effects observed when crossing mSOD1 mice with knockouts in pathways that are thought to be important to disease pathology at the cellular level, such as p75 (Küst et al, 2003) FasL−/− (Petri et al, 2006) or Bax−/− (Gould et al, 2006) null mice. In contrast, crossing Loa mice with mSOD1 mice showed some rescue effects both in axonal transport defects and in the life span of the mice (Kieran et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulation of proNGF, p75NTR and sortilin was also associated with spongiform encephalomyelopathy [52]. Reduced p75NTR delayed disease onset in female transgenic ALS mice [19], though treatment with a p75NTR antagonist showed no improvement on disease progression [53]. Furthermore, while the lactacystin and 6-OHDA rat models of PD were used in this study, previous evidence showed that they might differ in their mechanism to induce neuronal death; lactacystin might inhibit proteasomes and induce modified protein, and 6-OHDA might function through oxidative stress and induce mitochondrial dysfunction [1,5,6].…”
Section: Resultsmentioning
confidence: 99%
“…The proNGF triggers neuronal cell apoptosis by high-affinity binding to p75NTR, while p75NTR mediates neuronal cell death by formation of the p75NTR-sortilin signaling complex [9,12,13]. In fact, proNGF, p75NTR and sortilin exhibited roles in neurodegeneration of aging, onset or progression in various neurodegenerative diseases like Alzheimer’s disease (AD), amyotrophic lateral sclerosis (ALS) and acute trauma of the nervous system [1419]. Currently, however, there is still a lack of studies on the implication of proNGF-p75NTR-sortilin signaling in pathogenesis or progression of PD.…”
Section: Introductionmentioning
confidence: 99%